Revisão da seção setacea do gênero Batrachospermum (Rhodophyta, Batrachospermales) - Rossignolo, Natalia Leocadio [UNESP] (2014)
Section Setacea of the genus Batrachospermum was recognized as a monophyletic group in a recent revision of the order Batrachospermales. However, its taxonomic status was not clearly determined because it was positioned within a group named Australasica composed by taxa from Australia and New Zealand. Previous studies combining molecular and morphological data focused only on the phylogenetic relationships among the major groups (genera or sections), whereas approches aiming to evaluate the number of species were initiated just recently and are still scarce and poorly sampled. Based on this background, the following hypotheses were tested in this study: 1) the section Setacea represents a monophyletic group within the order Batrachospermales; the recognition of the group associated to the fact that the genus Batrachospermum is paraphyletic could result in the raising of the section to a higher taxonomic level (possibly genus); 2) the species presently recognized in the section based on morphological characters will be confirmed by molecular evidence; in addition, other species (particularly cryptic species) are expected to be found and recognized within the section.This study aimed to: 1) infer the phylogenetic relationships of section Setacea with other groups (genera and sections) of the Batrachospermales, as well as the inter and intra-specific limits of variation for the species within the section based on sequence analysis for the rbcL and cox1 barcode region: 2) elaborate a revisionary study by reevaluating the diagnostic taxonomic characters for the species of the sectionin the light of the new molecular data. Fifteen samples were analyzed, thirteen from southern and southeastern Brazil and two from other continents (Asia - Japan; Europe - Spain). The specimens were collected in waters with low to moderate temperatures, slightly acidic, turbulent and mean to moderate oxygen concentrations (oligotrophic and oligosaprobic...